Morphine clearance in children: Does race or genetics matter? - Sadhasivam, MD, MPH, Senthilkumar; Krekels, MSc, Elke H. J.; Chidambaran, MD, Vidya; Esslinger, MPT, Hope R.; Ngamprasertwong, MD, Pornswan; Zhang, MD, MBA, Kejian; Fukuda, PhD, Tsuyoshi; Vinks, PharmD, PhD, Alexander A. (Journal of Opioid Management, 2012)
Objective: Interindividual variability in analgesic response and adverse effects of opioids because of narrow therapeutic indices are major clinical problems. Morphine is an opioid commonly used in children to manage perioperative pain. Although size and age often are considered primary covariates for morphine pharmacokinetic models, the impact of other factors important in personalizing care such as race and genetic variations on morphine disposition is not well documented. Design: Genotype blinded clinical observational pharmacokinetic study. One hundred forty-six African American and Caucasian children scheduled for elective outpatient adenotonsillectomy were enrolled in our prospective genotype blinded observational study with standard perioperative clinical care. Setting: Tertiary care pediatric institution. Interventions: Morphine bolus for intraoperative analgesia in children and pharmacokinetic analyses in different races. Main outcome measures: Pharmacokinetics and pharmacogenetics of intravenous morphine in a homogeneous pediatric outpatient surgical pain population were evaluated. Results: The authors observed that African American children have higher morphine clearance than Caucasian children. The increased clearance is directed toward the formation of morphine-3-glucuronide formation, rather than the formation of morphine-6-glucuronide. Common uridine diphosphate glucuronosyl transferase (UGT) 2B7 genetic variations (-161C>T and 802C>T) were not associated with observed racial differences in morphine’s clearance although the wild type of the UGT2B7 isozyme is more prevalent in the African Americans. Conclusions: Race of the child is an important factor in perioperative intravenous morphine’s clearance and its potential role in personalizing analgesia with morphine needs further investigation.